Establishment of Discipline Character and Responsibility Through Parenting Patterns - Soleh, Asep Muhamad; Sudarmaji, Heri; Setiyo, Setiyo; Putra, Bambang Wijaya; S, Sarah Jihan Khanna (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
Purpose of this study is to determine the character formation of discipline and responsibility through cadet parenting that has been carried out at the Palembang Civil Aviation Polytechnic. The parenting pattern is carried out by applying a strict schedule to the daily activities of the cadets based on the Cadets Code of Conduct. The research methodÂ  is a qualitative research with a descriptive research model, to see how to strengthen the character of Palembang Civil Aviation Polytechnic cadets through parenting patterns. Collecting data by interview, observation and documentation. The results of the study show that the parenting pattern that is carried out can shape the character of discipline and responsibility for the Palembang Civil Aviation Polytechnic cadets. Based on this research, the formation of the character of discipline and responsibility of cadets can be formed through parenting patterns. So that parenting patterns can continue to be carried out with further development to shape future generations in the aviation sector in Indonesia.